2005
DOI: 10.1093/toxsci/kfi097
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Voltage-Gated Potassium Currents by Gambierol in Mouse Taste Cells

Abstract: Ciguatera is a food poisoning caused by toxins of Gambierdiscus toxicus, a marine dinoflagellate. The neurological features of this intoxication include sensory abnormalities, such as paraesthesia, heightened nociperception, and also taste alterations. Here, we have evaluated the effect of gambierol, one of the possible ciguatera toxins, on the voltage-gated ion currents in taste cells. Taste cells are excitable cells endowed with voltage-gated Na+, K+, and Cl- currents (I(Na), I(K), and I(Cl), respectively). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 32 publications
5
67
0
Order By: Relevance
“…Compounds such as gambierol are described to be produced by G. toxicus dinoflagellates, but relatively little is known about their targets. Although sodium and potassium channels have been proposed in the literature as possible targets (Inoue et al, 2003;Ghiaroni et al, 2005;Louzao et al, 2006), very few papers can couple these targets to the intoxication symptoms (Cameron, 1993). In this article, we define VGPCs as a physiological target of gambierol, examine its selectivity and speculate on gambierol's role in CFS intoxications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds such as gambierol are described to be produced by G. toxicus dinoflagellates, but relatively little is known about their targets. Although sodium and potassium channels have been proposed in the literature as possible targets (Inoue et al, 2003;Ghiaroni et al, 2005;Louzao et al, 2006), very few papers can couple these targets to the intoxication symptoms (Cameron, 1993). In this article, we define VGPCs as a physiological target of gambierol, examine its selectivity and speculate on gambierol's role in CFS intoxications.…”
Section: Discussionmentioning
confidence: 99%
“…Since K v 1.2 is an important player in multiple sclerosis, gambierol might be considered as a lead compound in further study of the use of toxins in the treatment of pathogenic conditions. It has been suggested that the highly lipophilic gambierol molecules are expected to enter the lipid bilayer of the cell membranes and disrupt the normal lipid environment that surrounds the potassium channels and which would likely have effect on the channel operation (Ghiaroni et al, 2005). However, from our experiment where we tested the IV relationship in HK solution, we can conclude that at least the ion selectivity is not changed by gambierol since the reversal potential in control (−2.6 mV±2.3; n = 5) and with 35 nM gambierol (−5.7 mV±2.8; n = 3) is statistically not significantly different (P>0.05; n = 3) and in the range of the calculated reversal potential (…”
Section: Discussionmentioning
confidence: 99%
“…toxicus produces a variety of polyethers with potent biological activities, among which gambierol (19) is intriguing because it strongly inhibits voltage-gated K + channels with an IC 50 value of 1.8 ng/ml and is toxic to mice with LD 50 50 μg/kg (Ghiaroni et al 2005). Gambierol's mechanism of action is discussed in Chap.…”
Section: Gambierolmentioning
confidence: 99%
“…Gambierol has been reported to irreversibly inhibit K + currents in the nanomolar range in excitable taste cells (Ghiaroni et al 2005), with a maximum efficiency of 60%. In addition to affecting the K + current amplitude, gambierol significantly altered both activation and inactivation processes of K + currents, whereas it showed no significant effect on Na + or Cl − currents even at micromolar concentrations.…”
Section: Gambierol and Polyether Toxinsmentioning
confidence: 99%
“…3 5 Very recently, it has been reported that gambierol acts as a potent and subtype selective inhibitor of voltage gated potassium channels. 6,7 As is often the case for many marine natural products, due to their scarce natural abundance and the dif culties of chemical modi cation, the biological characteristics of many of these polycyclic ether molecules have not yet been fully investigated. An increasingly important and often sole solution to these supply problems is chemical total synthesis.…”
Section: Introductionmentioning
confidence: 99%